Impact on corporate image in the face of inclusion of LGBT communities in retail stores in Peru - Santa Cruz Jaime, Tania Karen (2021)
This article analyzes the impact on corporate image as a product of the inclusion of members of the lesbian, gay, bisexual and transgender (LGBT) community in a group of retail stores in Peru. Through a mixed methodology, it was sought to determine what are the perceptions of customers when seeing or interacting with people from these communities when visiting specialized clothing stores; and what is the influence of this interaction in the formation of the corporate image of these commercial establishments. Faced with discrimination in work spaces due to the sexual orientation of their workers and the absence of public policies in favor of LGBT communities, this study shows that non-inclusion is based on prejudices or stereotypes that lead to negative direct consequences and that, communicationally, not there is damage to the corporate image of companies in the public with which it interacts.